Corporate firm in a changing World economy - "Smidt, Marc De (ed.); Wever, Egbert (ed.)" (London, 1990)
This book examines the economic environment and phenomena of multinational business with reference to case studies of major multinational companies, including IBM, Philips, Nissan and Volvo. It assesses how the major theories explaining the response of companies to changes are borne out by the experience of individual firms.
Keywords: Economics